Additional Advantages for Agronomic Performance and Fruit Quality in Tomato Hybrids of the Saladette Type Derived from a Dwarf Male Parent - Lucas Medeiros Pereira; Gabriel Mascarenhas Maciel; Ana Carolina Silva Siquieroli; Ana Luisa Alves Ribeiro; Frederico Garcia Pinto; Brena Rodrigues Mota Ikehara; José Magno Queiroz Luz; Rickey Yoshio Yada; Camila Soares de Oliveira (Horticulturae)
Tomatoes have tremendous economic, social, and nutritional importance. Among the various types of tomatoes, the Saladette/Italian stands out as an important cultivar for both fresh consumption and industrial processing. The production of this vegetable requires investments exceeding USD 30,000.00. Strategies that increase productivity to offset these costs are fundamental. One proposal to increase yield potential in tomato is the production of new hybrids using dwarf male parents as donors through an organized backcross breeding scheme. The present study, therefore, evaluated possible improvements in the agronomic performance and fruit quality of Saladette hybrids obtained from crosses between normal and dwarf inbred lines. Seventeen tomato hybrids obtained from three backcrosses (BC1, BC2, and BC3) and two commercial cultivars as a control (cv. Bento and Vivacy) were evaluated. The data were analyzed using the Scott–Knott test, and artificial neural networks were used to study the dissimilarities among the hybrids. The hybrids obtained from the dwarf male parent exhibited morphological changes in the plants, including a reduction in internodes, a greater number of bunches per linear meter of plant, and biofortification of the fruits. Notably, from the second backcross onwards, increases in fruit productivity and quality were observed when creating hybrid combinations from dwarf male parents.